Origin of epicardium, it’s structural and functional role in heart heterogeneity formation - Pototskaya O.Yu. (Морфологія, 2008)
In this work the major features of proepicardium structure, morphogenetic processes of epicardial formation and structural & functional role of epicardium-derived cells have been analyzed. proepicardium presented by protrusions of lateral plate mesoderm (serosal mesothelium), located between the liver and venous sinus in avian, and in the region of septum transversum in mammalian; it contains three cell types and proepicardial extracellular matrix. The formation of epicardial layer is a result of the heart tube coating by proepicardium. Epicardial cells (except atrial region) undergo the process of epithelial-to-mesenchimal transformation, resulting in emergence of epicardium-derived cells. Last ones give rise to the next cell populations: smooth muscle cells, adventitial fibroblasts of coronary vessels, fibroblasts of heart fibrose skeleton, inter-stitial fibroblasts; differentiation of epicardium-derived cells into angio-, or hemangioblasts, cardiomyocytes stays controver-sial. Functional roles of these cells consist in their participation in processes of myocardial compactization, septation, forma-tion of endocardial cushions in AV-canal, heart fibrose skeleton, changing the passive mechanical properties of the cardiac wall, looping, differentiation of Purkinje fibers. Future researches will be connected with the defining of species features, their molecular basis and investigation of embryonic potentials of mature cells, differentiated from epicardium-derived cells.